Genetic basis of hereditary hypophosphataemic rickets and phenotype presentation in children and adults - Tavana, Nahid; Thilakavathy, Karuppiah; Kennerson, Marina L.; Ting, Tzer Hwu (Via Medica, 2021)
Hypophosphataemic rickets (HR) is a genetic disorder causing defects in the renal handling of phosphorus, resulting in rickets. HR can be classified into two groups. First- those with excess fibroblast growth factor 23(FGF23) levels, which are due to gene mutations in extrarenal factors and include X-linked dominant hypophosphataemic rickets (XLHR), autosomal dominant hypophosphataemic rickets (ADHR), autosomal recessive hypophosphataemic rickets (ARHR), and hypophosphataemic rickets with hyperparathyroidism. Second- those with normal or low FGF23, which are caused by gene mutations in renal tubular phosphate transporters and include hereditary hypophosphataemic rickets with hypercalciuria (HHRH) and X-linked recessive hypophosphataemic rickets. The radiographical changes and clinical features of rickets in various types of HR are similar but not identical. Short stature, bone deformities mainly in the lower limbs, and dental problems are typical characteristics of HR. Although the initial diagnosis of HR is usually based on physical, radiological, and biochemical features, molecular genetic analysis is important to confirm the diagnosis and differentiate the type of HR. In this review, we describe clinical and biochemical features as well as genetic causes of different types of HR. The clinical and biochemical characteristics presented in this review can help in the diagnosis of different types of HR and, therefore, direct genetic analysis to look for the specific gene mutation.